The Case Study Of 'IOI" Group - Ferdouse, Farzana (2007)
The core business of IOI Group is integrated oil palm plantation business with activities comprising of upstream cultivation of oil palam and downstream resource based manufacturing, which includes refinery, manufacturing of oleo-chemicals and specialty oils and fats.